Human NK cell deficiency as a result of biallelic mutations in MCM10. - Mace, Emily M; Paust, Silke; Conte, Matilde I; Baxley, Ryan M; Schmit, Megan M; Patil, Sagar L; Guilz, Nicole C; Mukherjee, Malini; Pezzi, Ashley E; Chmielowiec, Jolanta; Tatineni, Swetha; Chinn, Ivan K; et al. (J Clin Invest, 2020)
Human natural killer cell deficiency (NKD) arises from inborn errors of immunity that lead to impaired NK cell development, function, or both. Through the understanding of the biological perturbations in individuals with NKD, requirements for the generation of terminally mature functional innate effector cells can be elucidated. Here, we report a cause of NKD resulting from compound heterozygous mutations in minichromosomal maintenance complex member 10 (MCM10) that impaired NK cell maturation in a child with fatal susceptibility to CMV. MCM10 has not been previously associated with monogenic disease and plays a critical role in the activation and function of the eukaryotic DNA replisome. Through evaluation of patient primary fibroblasts, modeling patient mutations in fibroblast cell lines, and MCM10 knockdown in human NK cell lines, we have shown that loss of MCM10 function leads to impaired cell cycle progression and induction of DNA damage-response pathways. By modeling MCM10 deficiency in primary NK cell precursors, including patient-derived induced pluripotent stem cells, we further demonstrated that MCM10 is required for NK cell terminal maturation and acquisition of immunological system function. Together, these data define MCM10 as an NKD gene and provide biological insight into the requirement for the DNA replisome in human NK cell maturation and function.
Keywords: Alleles; Cell Cycle Checkpoints; Cell Differentiation; Cell Line; Codon, Nonsense; DNA Damage; Fatal Outcome; Female; Gene Knockdown Techniques; Heterozygote; Humans; Induced Pluripotent Stem Cells; Infant; Killer Cells, Natural; Male; Minichromosome Maintenance Proteins; Models, Immunological; Mutation; Mutation, Missense; Pedigree; Primary Immunodeficiency Diseases

Novel STAT1 Gain-of-Function Mutation Presenting as Combined Immunodeficiency. - Hartono, Stella P; Vargas-Hernandez, Alexander; Ponsford, Mark J; Chinn, Ivan K; Jolles, Stephen; Wilson, Keith; Forbes, Lisa R (J Clin Immunol, 2018)

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Yuan, Bo; Jhangiani, Shalini N; Muzny, Donna M; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult